Development and standardization of test systems based on filter paper and modified with vanillin reagent - Prokopets, Vadim; Zdoryk, Oleksandr; Georgiyants, Viktoria (ScienceRise: Pharmaceutical Science, 2017)
Reagents and analytical tools for rapid analysis should be standardized and lead to the requirements of the State Pharmacopoeia of Ukraine. Newsprint paper is used as the main analytical tool for rapid analysis of substances with primary aromatic amino group, but it can’t be standardized. The development of test systems based on filter paper and modified with pharmacopeia reagents can be the problem solution. Aim. The aim of the work is development and implementation of test-kits based on filter paper for rapid analysis of compounded preparations that contain primary aromatic amino group in conditions of pharmacies. Methods. Methods of physical immobilization; determination of physical stability of test kits; economic and statistical methods (cost calculation); validation of analytical methods; statistical methods of data processing chemical experiment. Results. Filter paper and pharmacopeia solution of vanillin were used to develop test systems; the possibility of using the test system in practice was investigated with the application of rapid analysis of sulfacetamide and sulfathiazole sodium. The possibility of using of the test system for rapid analysis of 5% aqueous solutions of derivatives of sulfanilic acid amides has been proved; the following detection limits and unreliability intervals for the rapid analysis method using test systems were established: 5.0-9.0 mg/ml for sodium sulfacetamide and 5.3-9.6 mg/ml for sodium sulfathiazole. The test system is stable during 5 months of storage. Manufacturing cost of 1 test system is 0.34 and 0.16 UAH for the first and the next batches, respectively. Conclusions. The proposed test system is stable and accessible for usage in pharmacy as an analytical tool for rapid analysis of derivatives of sulfanilic acid amides